Correlation of Attitudes towards Remote Consultations of a Rheumatologist with Health Locus of Control: Survey of Lithuanian Patients with Chronic Rheumatic Diseases (Baltic Journal of Sport and Health Sciences, 2022)
Background: During the COVID-19 pandemic, telemedicine has become an important means to control the disease with the help of a doctor for patients with chronic diseases. To make treatment of chronic rheumatic diseases effective, it is important that patients have a positive attitude towards the remote consulting and maintained health related individual behavior, which depends on the patient’s health locus of control.Methods: The sample of the survey consists of 207 Lithuanian patients with chronic rheumatic diseases. Most of them have been diagnosed with spondyloarthritis (n=83), connective tissue diseases (n=53) and rheumatoid arthritis (n=49). To reveal the attitude towards remote consultations of a rheumatologist, an original questionnaire has been developed, which includes reasons for prioritizing remote consultations of a rheumatologist, and positive and negative attitude towards the consultations. Health locus of control was assessed by Multidimensional Health Locus of Control (MHLC) scale, which contains Internality, Chance and Powerful Others subscales.Results: The survey revealed the main reasons why patients with chronic rheumatic diseases choose remote consultations. When comparing the average of statements revealing positive attitude M=2.78 with the negative one of M=1.51 it becomes obvious that the attitude of subjects towards remote consultations is favorable. A correlation analysis was performed to assess the correlation of patient positive or negative attitudes towards remote consultations with the health locus of control. The results did not establish a correlation between patients’ positive attitude towards the named consultations and internality locus of control. However, it has been obtained that a negative attitude towards remote consultations has albeit not strong, but a statistically significant correlation with two indicators of health locus of control – Chance (r=0.203, p≤0.0001) and Powerful Others (r=0.94, p=0.01).Conclusion: The survey revealed a favorable attitude of patients with chronic rheumatic diseases towards remote consultations. Furthermore, it showed that personal conviction of a patient that health depends on circumstances and influence of other people worsens the attitude towards remote consultations.Keywords: telerheumatology, remote consultations, health locus of control.